HGIS AND ARCHIVE RESEARCHES: A TOOL FOR THE STUDY OF THE ANCIENT MILL CHANNEL OF CESENA (ITALY) - G. Bitelli; F. Bartolini; G. Gatta (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2016)
The present study aims to demonstrate the usefulness of GIS to support archive searches and historical studies (e.g. related to industrial archaeology), in the case of an ancient channel for mill powering near Cesena (Emilia-Romagna, Italy), whose history is weaved together with the history of the Compagnia dei Molini di Cesena mill company, the most ancient limited company in Italy. Several historical maps (about 40 sheets in total) inherent the studied area and 80 archive documents (drawings, photos, specifications, administrative acts, newspaper articles), over a period of more than 600 years, were collected. Once digitized, historical maps were analysed, georeferenced and mosaicked where necessary. Subsequently, in all the maps the channel with its four mills and the Savio river were vectorized. All the additional archive documents were digitized, catalogued and stored. Using the QGIS open source platform, a Historical GIS was created, encompassing the current cartographic base and all historical maps, with their vectorized elements; each archive document was linked to the proper historical map, so that the document can be immediately retrieved and visualized. In such a HGIS, the maps form the base for a spatial and temporal navigation, facilitated by a specific interface; the external documents linked to them complete the description of the represented elements. This simple and interactive tool offers a new approach to archive searches, as it allows reconstruction in space and time of the evolution of the ancient channel and the history of this important mill company.